Cultural identity in the Roman Empire - Laurence, Ray, 1963-; Berry, Joanne, 1971- (Routledge, 1998)
This provocative and often controversial volume examines concepts of ethnicity, citizenship and nationhood, to determine what constituted cultural identity in the Roman Empire. The contributors draw together the most recent research and use diverse theoretical and methodological perspectives from archaeology, classical studies and ancient history to challenge our basic assumptions of Romanization and how parts of Europe became incorporated into a Roman culture. Cultural Identity in the Roman Empire breaks new ground, arguing that the idea of a unified and easily defined Roman cultu.
Keywords: Acculturation -- Rome.; Romans -- Cultural assimilation -- Sources.; Rome -- Cultural policy -- Historiography.; Citizenship -- Rome.; Fiction -- Cultural assimilation -- Sources.; Roman -- Acculturation -- Sources.; Citoyenneté -- Rome.; Rome -- Politique culturelle -- Historiographie.; Romains -- Acculturation -- Sources.; Éducation au développement -- Rome.; POLITICAL SCIENCE -- Globalization.; Acculturation; Citizenship; Cultural policy -- Historiography; Romans -- Cultural assimilation; Rome (Empire); Electronic books.; Sources